Time and anti-realism in modern and contemporary Irish novels - Li, Lianghui (Nanyang Technological University, 2021)
The connection between narrative and time in literary criticism is informed by the rising temporal self-consciousness in the novel in the second half of the twentieth century. Two trends have commenced from this period: the narrative present and narrative self-reflexivity. This study seeks to explore how narrative time is informed by narrative experiments while interrogating retrospective narration. Narrative time is approached from two aspects: narrative self-reflexivity that distinguishes narrated time from time of narration, and linguistic experimentation with the use of tense and time deixis. Examining works by Samuel Beckett, John Banville, Anne Enright, Mike McCormack, and Sara Baume, I argue that the anti-realist impulse in these novels reveals narration as non-retrospective and a process of re-conceptualizing time. This conceptual process celebrates presentation and rendition rather than representation and reconstruction for the sake of narrative linearity. Despite their concerns with the historical and personal issues, these Irish novels produce an experience of alternative time and even a process of self-creation. This study simultaneously aims to chart the evolution of the anti-realist thrust in Irish novels, especially in recent decades. It is within this anti-realist tradition that narration and time are intensely contested and explored. From Beckett to Baume, the featuring of narrative self-reflexivity decreases. Yet, the selected novels offer a battleground between realist and anti-realist aspects, and thus foreground an impulse of experimentation that persists in the contemporary Irish novel. While the narrators in these novels engage with the fabrication of time, their Irish authors retain certain detachment from their times by paying homage to the anti-realist tradition.